IBS in Residential Projects; Dissolving the Problems of On-site Component Installation - Ahmad, Abd Jalil; Shazwan, Mohamed Shaari; Nurina, Nawi (2021)
Installation the IBS components require detail precision and proper process, if not, the IBS adoption will not bring faster and cheaper cost but instead expose to spending more time for rectification of the defective works. Identifying the difficulties in conducting installation of IBS components is paramount, which need detail supervision work. Without proper supervision during installation, the IBS in residential projects will not only expose to delay, quality disputes, and design clashes but will also cause misconceptions and coordination problems. The objective of this research is to discover the problems that mostly occur during IBS components installation at site and propose ways to avoid those problems. Besides, the bad effects of the installation problems were also discuss based on the perspective of every stakeholder who involve in IBS residential projects. A questionnaire survey comprising 26 questions was designed in this study to ascertain the challenges/suggestions regarding current practice on IBS installation and its supervision in housing projects. To further validate the collected data, semi-structured interviews were conducted to solicit views from experienced IBS practitioners. The results reveal that the main challenges in supervising to install IBS components are on hardly to find skillful supervision team, supervision additional fees, and IBS components handling. As for solution, most respondents agreed that the IBS installation can be improved by regulating for supervision as mandatory, provide clearer method statement and constant monitoring. At present, most contractors choose to install the IBS components without having supervision as this require fees, and thus many installation facing defects problems. As conclusion, IBS targets for better quality, cost effective and faster completion for Malaysian residential projects is hard to achieve due to lack attention on dissolving the problems involving components installation.